Dominant modal decomposition method. (31st March 2017) - Dombovari, Zoltan
Abstract: The paper deals with the automatic decomposition of experimental frequency response functions (FRF׳s) of mechanical structures. The decomposition of FRF׳s is based on the Green function representation of free vibratory systems. After the determination of the impulse dynamic subspace, the system matrix is formulated and the poles are calculated directly. By means of the corresponding eigenvectors, the contribution of each element of the impulse dynamic subspace is determined and the sufficient decomposition of the corresponding FRF is carried out. With the presented dominant modal decomposition (DMD) method, the mode shapes, the modal participation vectors and the modal scaling factors are identified using the decomposed FRF׳s. Analytical example is presented along with experimental case studies taken from machine tool industry.